2021
DOI: 10.3390/ijms22147406
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of EMILIN-1 by Proteolysis and Secretion in Small Extracellular Vesicles Favors Melanoma Progression and Metastasis

Abstract: Several studies have demonstrated that melanoma-derived extracellular vesicles (EVs) are involved in lymph node metastasis; however, the molecular mechanisms involved are not completely defined. Here, we found that EMILIN-1 is proteolyzed and secreted in small EVs (sEVs) as a novel mechanism to reduce its intracellular levels favoring metastasis in mouse melanoma lymph node metastatic cells. Interestingly, we observed that EMILIN-1 has intrinsic tumor and metastasis suppressive-like properties reducing effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…One limitation of our study is that due to the complete absence of nodal metastases in the FVB MMTV-Δ16HER2 mouse model, we could not assess the impact of EMILIN1 loss on the maintenance of lymphatic homeostasis and the regulation of lymph nodal spreading, as previously observed in other cancer types 14 , 28 , 40 . Nonetheless, our study of human breast cancer samples revealed a significant decrease in EMILIN1 expression in metastatic lesions, most of which were collected from lymph nodal locations.…”
Section: Discussionmentioning
confidence: 96%
“…One limitation of our study is that due to the complete absence of nodal metastases in the FVB MMTV-Δ16HER2 mouse model, we could not assess the impact of EMILIN1 loss on the maintenance of lymphatic homeostasis and the regulation of lymph nodal spreading, as previously observed in other cancer types 14 , 28 , 40 . Nonetheless, our study of human breast cancer samples revealed a significant decrease in EMILIN1 expression in metastatic lesions, most of which were collected from lymph nodal locations.…”
Section: Discussionmentioning
confidence: 96%
“…EMILIN1 produced by vascular smooth muscle cells is a major regulator of resting blood pressure levels (Litteri et al., 2012 ). Interestingly, EMILIN1 is proteolyzed and secreted in small EVs as a mechanism to reduce its intracellular level (Amor López et al., 2021 ). Smooth muscle cells in the vasculature undergo a number of changes in response to acute exercise (Newcomer et al., 2011 ), secrete EVs in vitro and in vivo (Kapustin & Shanahan, 2016 ), and are responsive to EV signalling from vascular endothelial cells in vitro (Boyer et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the EMILIN family can induce tumor cell apoptosis by mimicking classical extracellular apoptosis pathways, and may be involved in regulating tumor angiogenesis by interacting with other extracellular matrix components or cell surface molecules ( 51 ). A Gene expression study in human NSCLC revealed that increased expression of EMILIN1 was associated with low proliferation of tumor cells ( 52 ). S100A8 belongs to the S100 protein family which is closely related to the regulation of intracellular Ca 2+ , cell proliferation, differentiation, movement, and apoptosis, and other cell functions ( 53 ).…”
Section: Discussionmentioning
confidence: 99%